(untitled) (ACME, 2020)
Between the Fifteenth and Sixteenth centuries, i.e. before the printing of Il ritratto di Milano by Carlo Torre (1674), there are many foreigners who publish descriptions of Milan. In addition to that contained in the well-known Relatione della città e stato di Milano by Galeazzo Gualdo Priorato (1666), there are numerous descriptions included in geo-historical repertoires, variously elaborated in the form of travel itineraries, cosmographies or universal histories. However, these descriptions are not always or completely the result of direct experiences. Indeed, very often they are the result of recycling operations, so that at the time of publication these texts appear inconsistent or even outdated. Because of their – sometimes only supposed or partial – inaccuracy or unreliability, art historians have considered these descriptions of Milan very little. However, a careful and patient reading allows us to recover, beyond reuse and errors, not a little information practically unknown to the academia. This is a “research test” developed on four of these descriptions, an example to prove what can be discovered by probing this paradoxically unexplored terrain. In closing, some reflections on the Milanese periegetic materials produced by locals.